Oils from different vegetal sources as precursor materials influencing essential physicochemical characteristics of the biodiesel obtained via the transesterification reaction - Hernández-Terrones, Manuel Gonzalo; Portela, Flaysner Magayver; Melo, Patrícia Gontijo; Queiroz, Douglas Santos; Borges Neto, Waldomiro; Domingos Fabris, José (Eclética Química, 2015)
A set of physicochemical properties, viz acidity, color, density, saponification, kinematic viscosity, free glycerol, carbon residue and oxidation stability, were determined for transesterification products from methyl and ethyl alcohol reactions with triacylglycerides of oil-rich natural substrates extracted from fruits of traditionally cultivated plants, namely corn (Zea mays), soybean (Glycine max), sunflower (Helianthus annuus) and rapeseed (Brassica napus), and from three other species: physic nut (Jatropha curcas), pequi (Caryocar brasiliense) and macaúba palm (Acrocomia aculeate), which are of potential commercial value for the industrial production of biodiesel. The obtained data were compared with the main officially recommended certification indexes. Oils from the two native species from the Brazilian flora, Acrocomia aculeate and Caryocar brasiliense, were confirmed to have real commercial potentiality to produce biodiesel.